The Effectiveness of Physical Exercise in Stroke Patient Recovery: A Systematic Review - Denny Christian Lukas; Williem Harvey; Meilisa Sri Suzana (CV. Inara, 2024)
Background: Stroke is a leading cause of disability worldwide, significantly affecting motor function, mobility, and patients’ quality of life. Physical exercise is often recommended as part of rehabilitation programs to enhance recovery after a stroke. Objective: This study aims to systematically review the literature on the effectiveness of physical exercise in accelerating post-stroke recovery, particularly in improving motor function, mobility, and independence. Methods: A systematic search was conducted across electronic databases such as PubMed, Scopus, and ScienceDirect using keywords like